Management of parking space in UiTM Shah Alam / Muhamad Fithri Norizan - Norizan, Muhamad Fithri (Faculty of Architecture, Planning and Surveying, 2014)
The management of parking space is important in all areas. It covers aspects such as administrative, planning, strategies, facilities, work frame, maintenance and satisfaction of end-users. There are general purpose and definition of management of parking space. The aim of facilities management is to support and improve the system of parking in terms of maximizing the usage of the facilities, smoothest the flow of the system, the safety, the space, and without impairing environmental qualities. Departments that are involved in the management of parking space in campus are different compared to other areas. In this research, MARA University of Technology (UiTM) Shah Alam was chosen as a case study. This institution is chosen because UiTM Shah Alam has a management system that is managed by its own unit. The objective of this research is to identify the problems and effectiveness of parking space management in UiTM Shah Alam. In addition, the objective is also to evaluate the satisfaction level of the user on management of parking space. The method carried out was through questionnaires and analysis. Then, after the analysis of all the data and information, recommendations are given on the problems stated. In generally, the facilities management for management of parking space is essential for planning, controlling, and to prevent problems such as insufficient parking space. Monitoring from time to time and introducing new technologies used is essential to ensure the effectiveness of quality facilities management.